Histamine H3 and H4 receptors modulate Parkinson's disease induced brain pathology. Neuroprotective effects of nanowired BF-2649 and clobenpropit with anti-histamine-antibody therapy - Sharma A.; Muresanu D.F.; Patnaik R.; Menon P.K.; Tian Z.R.; Sahib S.; Castellani R.J.; Nozari A.; Lafuente J.V.; Buzoianu A.D.; Skaper S.D.; Bryukhovetskiy I.; Manzhulo I.; Wiklund L.; Sharma H.S. (My University, 2025)
Military personnel deployed in combat operations are highly prone to develop Parkinson's disease (PD) in later lives. PD largely involves dopaminergic pathways with hallmarks of increased alpha synuclein (ASNC), and phosphorylated tau (p-tau) in the cerebrospinal fluid (CSF) precipitating brain pathology. However, increased histaminergic nerve fibers in substantia nigra pars Compacta (SNpc), striatum (STr) and caudate putamen (CP) associated with upregulation of Histamine H3 receptors and downregulation of H4 receptors in human cases of PD is observed in postmortem cases. These findings indicate that modulation of histamine H3 and H4 receptors and/or histaminergic transmission may induce neuroprotection in PD induced brain pathology. In this review effects of a potent histaminergic H3 receptor inverse agonist BF-2549 or clobenpropit (CLBPT) partial histamine H4 agonist with H3 receptor antagonist, in association with monoclonal anti-histamine antibodies (AHmAb) in PD brain pathology is discussed based on our own observations. Our investigation shows that chronic administration of conventional or TiO2 nanowired BF 2649 (1 mg/kg, i.p.) or CLBPT (1 mg/kg, i.p.) once daily for 1 week together with nanowired delivery of HAmAb (25 μL) significantly thwarted ASNC and p-tau levels in the SNpC and STr and reduced PD induced brain pathology. These observations are the first to show the involvement of histamine receptors in PD and opens new avenues for the development of novel drug strategies in clinical strategies for PD, not reported earlier. © 2021 Elsevier B.V.